Identification and characterization of the activated defence response in the commercially important Agarophyte, Gracilaria Gracilis, following exposure to disease elicitors - Ealand, Christopher Shawn (Department of Molecular and Cell Biology, 2014)
To our knowledge, this study represents the first analysis of gene expression using cDNA microarrays in the red macroalga G. gracilis. Western hybridization analysis was used to establish whether the observed changes in gene expression following exposure to disease elicitors positively correlated to changes at the protein level.